Traffic Safety Impact Factors Related to Changing the Vehicles Among Drivers in Closed Systems - Božović, Milan; Pešić, Dalibor; Davidović, Jelica; Antić, Boris; Simeunović, Milan (Promet - Traffic&Transportation, 2022)
Work-related road accidents are estimated to con-tribute to at least one quarter to over one third of all work-related deaths. Changing the vehicle has a major impact on traffic safety. Some studies have shown that drivers’ knowledge and practical driver training can improve traffic safety when changing vehicles. The aim of this paper is to determine whether there is an impact of the vehicle change on traffic safety. The research was conducted at the location with cylinders, braking coeffi-cient sensors, and brake pedal force detector, as well as with ten different passenger car brands and types. At the time of the research, all cars were registered and used daily in traffic. Prior to the research, the precision of the measuring instruments at the research site was checked. On the basis of the results, it can be concluded that there are two significant factors: the vehicle and the driver who needs to be trained before starting to drive a new ve-hicle. When changing the vehicle brand and type within the company, it is necessary to conduct systemic training of drivers which would include theoretical and practical parts and involve at least braking, driver distraction, and active and passive vehicle safety.